Fenomena Fear of Missing Out (FoMO) Pasca Hegemoni Media Sosial Digital di Indonesia dalam Perspektif Skizoanalisis Gilles Deleuze - Erliyana Devitasari; John Abraham Ziswan Suryosumunar (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2023)
This article is a scientific paper in the field of philosophy. The material object of this article is the phenomenon of fear of missing out (FoMO) after digital social media hegemony in Indonesia. The formal object is the schizoanalysis perspective from Gilles Deleuze. The analysis using philosophical hermeneutic method, it was found that the phenomenon of fear of missing out (FoMO) has a correlation with the development of contemporary culture that is supported by the increase of digital social media users. This phenomenon is a form of anxiety when comparing oneself with what is owned and experienced by others, which then encourages each individual to consume everything that is considered trending to increase their symbolic appreciation of it. From the perspective of schizoanalysis, this phenomenon is a form of epistemological madness. There is disconnection between reality and the orientation of thought that is presented through various symbolic attributes due to the hegemony of digital social media. This condition is considered by Deleuze as the foundation of representative truth that curbs the emergence of change.